MODEL PEMBERDAYAAN EKONOMI PEREMPUAN MELALUI GRASSROOT MICROFINANCE SYARIAH - Rohmah, Siti (Sawwa: Jurnal Studi Gender dan Anak, 2014)
The focus of this research is to analyze models of empowerÂment of women in the work area DPU Tauhid Daarut Bandung and its influence on family income. The purpose of this study is to analyze models of empowerment of women in the work area DPU Tauhid Daarut London and Her influence to increase family income. The existence of this study are expected to be knowledgeable about the model of womens empowerment as an effort to increase womens economic although it can be sold in other regions indonesia. The results showed that the model of the empowerment of women in the DPU Daarut Tauhid is a semi-direct model of mentoring faith based. The existence of an impact empowerment efforts on improving the quality of life with the motivation to change for the better so that increasing family income, a culture of saving, as well as cooperation among its members.